If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=(x+9)+2x
We move all terms to the left:
3x-((x+9)+2x)=0
We calculate terms in parentheses: -((x+9)+2x), so:We get rid of parentheses
(x+9)+2x
We add all the numbers together, and all the variables
2x+(x+9)
We get rid of parentheses
2x+x+9
We add all the numbers together, and all the variables
3x+9
Back to the equation:
-(3x+9)
3x-3x-9=0
We add all the numbers together, and all the variables
-9!=0
There is no solution for this equation
| x+1.4=-6.1 | | 12x/36=8 | | (x+1)+(2x-13)=24 | | 7/x=5/9-x | | (4x-3)/(2x+1)=0 | | 7=r/9 | | -6y+4(y-5)=-12 | | 4(-x+3)=-2(-x-1) | | 6k-12=-12-12k | | q/3-4=3 | | 429=d+970 | | 12–3v=3 | | 16d+23=14(d−2)- | | -20=4x-66x | | 30=2w | | 0.6x-5=0.1x=7 | | 4×3=2b-7 | | 8+7/10x=6+1/5x | | 2×(x+5)=8+3×(x-5) | | 60=4k | | s3– 1= 1 | | 9((1+x)=8x | | a+67=95 | | d+15=86 | | -5x+2(3x-7)=12 | | 6x+14=3(2x+5) | | 12x-5=5x+30 | | 1/9x+7=17 | | −12(x+2)+112x=3x=1x=2x=4x=5 | | |7v-1|+6=33 | | -3x+1=-5x-11 | | 10+g/4=42 |